Why are you eating, mom? Maternal emotional, restrained, and external eating explaining children's eating styles. (1st October 2019) - Zarychta, Karolina; Kulis, Ewa; Gan, Yiqun; Chan, Carina K.Y.; Horodyska, Karolina; Luszczynska, Aleksandra
Abstract: This study investigated if three maternal eating styles (emotional eating style, external eating style, and restrained eating style) predict respective eating styles in children. In particular, we tested if these associations are different in mother-daughter dyads, compared to mother-son dyads. Data were collected twice, at the baseline (Time 1; T1) and at the 10-month follow-up (Time 2; T2), with N = 822 mother-child dyads participating at T1. Children (55% girls, 5–12 years old, M = 8.21, SD = 1.40) were interviewed; mothers (aged 23–59 years old, M = 35.93, SD = 5.24) completed the questionnaire assessing their eating styles. Participants' weight and height were measured objectively. Path analysis, accounting for dyadic interdependency and autocorrelations, was applied. In mother-daughter dyads, maternal emotional eating (T1) predicted daughters' emotional eating (T2) whereas maternal restrained eating (T1) predicted daughters' restrained eating (T2). There were no effects of external eating in mother-daughter dyads. A different pattern of associations was found for mother-son dyads, with maternal emotional eating (T1) and external eating (T1) predicting sons' emotional eating (T2) and external eating (T2), respectively. There was no effect of maternal restrained eating in mother-son dyads. Maternal eating styles explain child's eating styles with distinct effects depending on child's sex. Educating mothers about the effects of their own eating styles on daughters' and sons' eating styles might be useful to promote adequate responses to hunger and satiety signals.